2007
DOI: 10.1007/s11664-006-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Phase Equilibria of Sn-Cu-Au Ternary and Ag-Sn-Cu-Au Quaternary Systems and Interfacial Reactions in Sn-Cu/Au Couples

Abstract: The phase equilibria of the Sn-Cu-Au ternary, Ag-Sn-Cu-Au quaternary systems and interfacial reactions between Sn-Cu alloys and Au were experimentally investigated at specific temperatures in this study. The experimental results indicated that there existed three ternary intermetallic compounds (IMCs) and a complete solid solubility between AuSn and Cu 6 Sn 5 phases in the Sn-Cu-Au ternary system at 200°C. No quaternary IMC was found in the isoplethal section of the Ag-Sn-Cu-Au quaternary system. Three IMCs, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Both diagrams suggested that a continuous solid solution exists between the Cu 6 Sn 5 phase and the AuSn phase. 12,13 In the present study, the reflow temperature (250°C) falls within the range of 200°C to 360°C, so the interfacial reaction product at the Sn/Cu interface should likely be the ternary Au-Cu-Sn solid-solution phase.…”
Section: Sn/cu Interfacial Reaction In An Au/sn/cu Sandwich Structurementioning
confidence: 77%
“…Both diagrams suggested that a continuous solid solution exists between the Cu 6 Sn 5 phase and the AuSn phase. 12,13 In the present study, the reflow temperature (250°C) falls within the range of 200°C to 360°C, so the interfacial reaction product at the Sn/Cu interface should likely be the ternary Au-Cu-Sn solid-solution phase.…”
Section: Sn/cu Interfacial Reaction In An Au/sn/cu Sandwich Structurementioning
confidence: 77%
“…However, these phases are kinetically not easy to form and have not been observed in the ternary phase diagram determinations [20,23].…”
Section: Resultsmentioning
confidence: 99%
“…It could be a very fine eutecticlike mixture of the AuSn 4 and (Cu,Au) 6 Sn 5 phases or a new AuSn-Cu ternary phase. However, a ternary phase with this composition has never been reported [20,23]. Further studies are needed to characterize this phase region.…”
Section: Resultsmentioning
confidence: 99%
“…This metallurgical treatment method has been applied in several systems. 10,11,[18][19][20][21] Optical microscopy (OM) and scanning electron microscopy (SEM) were used to observe the surface morphology. The compositions of the IMCs formed at the interface were determined using electron probe microscopy analysis (EPMA).…”
Section: Methodsmentioning
confidence: 99%